2012
DOI: 10.1002/ffj.3107
|View full text |Cite
|
Sign up to set email alerts
|

Changes in strawberry volatile sulfur compounds due to genotype, fruit maturity and sample preparation

Abstract: Nineteen volatile sulfur compounds (VSCs), including ten thioesters and eight alkyl sulfides, were quantified using solid phase microextraction–gas chromatography–pulsed flame photometric detection in 12 Florida strawberry cultivars. The major headspace VSCs in all 12 cultivars were methanethiol and methyl thioacetate, together comprising 77–95% of the total VSCs. Concentrations for the 13 major strawberry VSCs were determined at five maturity stages. Puréed fruit produced 10–20 times more headspace volatiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…The SPME fiber coating is one of the most important factors affecting extraction efficiency, because different coating materials have different absorption efficiencies (Spietelun and others ). Several studies have reported different fibers being used for analyzing the content of VSCs in different foods (Hill and Smith ; Mestres and others ; Fang and Qian ; Miracle and others ; Du and others ). In the present study, 5 SPME fibers (PDMS, PDMS/DVB, CAR/PDMS, DVB/CAR/PDMS, and PA) were tested for their efficiency at extracting VSCs from Chinese liquor.…”
Section: Resultsmentioning
confidence: 99%
“…The SPME fiber coating is one of the most important factors affecting extraction efficiency, because different coating materials have different absorption efficiencies (Spietelun and others ). Several studies have reported different fibers being used for analyzing the content of VSCs in different foods (Hill and Smith ; Mestres and others ; Fang and Qian ; Miracle and others ; Du and others ). In the present study, 5 SPME fibers (PDMS, PDMS/DVB, CAR/PDMS, DVB/CAR/PDMS, and PA) were tested for their efficiency at extracting VSCs from Chinese liquor.…”
Section: Resultsmentioning
confidence: 99%
“…Later studies on strawberry sulfur compounds showed that a puree process in the experimental pretreatment of strawberries affected the analysis of volatile sulfur compounds; except for methanethiol, the dimethyl disulfide and dimethyl trisulfide in the puree exhibited lower amounts while most sulfur compounds were similar to, or higher than, those in intact strawberries . Principal component analysis (PCA) of sulfur compounds among 12 strawberry cultivars showed differences in constituents and in the amounts of sulfur compounds in a cultivar dependent manner; for instance, ‘Strawberry Festival’ and ‘Florida Radiance’ possessed high thioester concentrations, whereas ‘Dover’, ‘Rosa Linda’, and ‘Florida Belle’ contained higher sulfide and lower thioester concentrations . Through the measurement of these sulfur compound OAVs, methanethiol was determined to be the predominantly active volatile sulfur compound …”
Section: Characteristic Volatile Compounds In Strawberrymentioning
confidence: 99%
“…Research indicates that although the association of furanone content with cultivar is strong, these volatiles do increase with ripening (Pérez et al, ), thus explaining the differences noted in under‐ripe and ripe strawberries. Fermented flavor is produced as a result of alcohol compounds present in strawberry fruit, of which have been reported to develop upon fruit ripening (Dirinck et al, ; Du et al, ; Forney et al, ; Larsen & Watkins, ), thus fruit of a ripe maturation stage are expected to possess this attribute to a greater degree.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is limited research evaluating the sensory characteristics of strawberries grown in the cooler climates of Australia, with many Australian grown strawberries bred overseas (Horticulture Australia Limited, ). Strawberry flavor is characterized by complex interactions between volatile and nonvolatile components, together with the sugars and organic acids (Aubert, Baumann, & Arguel, ; Azodanlou, Darbellay, Luisier, Villettaz, & Amadò, ), the combination unique to different cultivars and dependent upon maturation stage (Aaby, Mazur, Nes, & Skrede, ; Dong, Zhang, Tang, Jin, & Han, ; Du, Whitaker, & Rouseff, ; Forney, Kalt, & Jordan, ; Kafkas et al, ; Montero et al, ; Pérez, Olías, Sanz, & Olías, ; Sturm et al, ). Given the diversity in chemical composition, and subsequently fruit flavor according to cultivar, maturation level and climate, it is important to devise a descriptive language to distinguish between fruit of different cultivars at various stages of ripening.…”
Section: Introductionmentioning
confidence: 99%